Strategic Management in Creative Industries and Its Effectiveness Measurement - Riabko, Natalija (The Applied Business & Management Review, 2025)
This article examines the application of strategic management practices within creative industries—specifically theaters and museums—and evaluates methods for assessing their effectiveness. Operating at the intersection of culture, technology, and economics, creative organizations face unique challenges, including digital transformation, cybersecurity risks, and performance measurement complexities. Through a case study approach and two tailored questionnaires, the study evaluates management practices and cybersecurity awareness across cultural institutions in five EU countries. Findings reveal that while cybersecurity awareness is generally strong, there are significant gaps in management effectiveness, even among EU-subsidized organizations. The study emphasizes the need for structured strategic planning, effective role distribution, and inclusive governance to enhance productivity, innovation, and resilience in creative sectors. Additionally, the research highlights the integration of information security into strategic frameworks as a critical factor in safeguarding digital cultural heritage. It argues for a shift from rigid bureaucratic models to adaptive, decentralized structures capable of responding to dynamic environments. The paper also explores performance evaluation frameworks, combining qualitative and quantitative indicators, and underscores the role of cultural policy in balancing artistic freedom with operational efficiency. Ultimately, the study contributes to cultural management theory by presenting actionable recommendations for optimizing strategic decision-making, employee engagement, and digital resilience in creative industries. The article calls for continued research and larger-scale data collection to further validate and refine its findings.